2006
DOI: 10.2174/138161206776389822
|View full text |Cite
|
Sign up to set email alerts
|

Whole Embryo Culture: An Important Tool in Developmental Toxicology Today

Abstract: The number of candidate chemicals or drugs for registration and authorization is increasing at a fast rate and only few of the existing substances have been tested for teratogenicity to date. Therefore, there is high pressure on authorities to accept models like the whole embryo culture as a screening system for safety evaluation procedures. In view of this background the gradual development of the whole embryo culture into a standardized, scientifically validated tool for developmental toxicology during the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 140 publications
(239 reference statements)
0
10
0
Order By: Relevance
“…In this assay, the embryo is removed from its dam and cultured for 1–2 days to allow developmental progress in vitro (New, ; Ellis‐Hutchings and Carney, ). In developmental toxicology studies, the advantage of whole‐embryo culture over animal‐based tests is that abnormalities in embryos can be directly related to the concentration of the drug being tested, which may then be compared to the serum concentration present in humans (Webster et al, ; Flick and Klug, ). Here, embryos were dissected from euthanized pregnant mice at 8.5 dpc, and cultured for 24 hr with or without 10 µM of donepezil.…”
Section: Resultsmentioning
confidence: 99%
“…In this assay, the embryo is removed from its dam and cultured for 1–2 days to allow developmental progress in vitro (New, ; Ellis‐Hutchings and Carney, ). In developmental toxicology studies, the advantage of whole‐embryo culture over animal‐based tests is that abnormalities in embryos can be directly related to the concentration of the drug being tested, which may then be compared to the serum concentration present in humans (Webster et al, ; Flick and Klug, ). Here, embryos were dissected from euthanized pregnant mice at 8.5 dpc, and cultured for 24 hr with or without 10 µM of donepezil.…”
Section: Resultsmentioning
confidence: 99%
“…The screening approach using the chorioallantoic membrane of the developing rat embryo [11], [28] showed that the supernatant obtained from HMEC-1 stimulated by shear stress elicited an angiogenic effect in comparison to control ( Figure 1 .A ). Gestational day 9.5 rat embryos were cultured for 48 h. This time period during embryogenesis covers a major part of organogenesis, when a complex vasculature is developed in the yolk sac as well as in the embryo itself.…”
Section: Resultsmentioning
confidence: 99%
“…After identification and synthesis of Up 4 U, the angiogenic effects of synthetic Up 4 U were verified using the assay whole embryo culture system [11], [28]. Figure 1 .C demonstrates the impact of Up 4 U on the morphological pattern of the vascularisation of the yolk sac membrane.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The review authored by Flick and Klug [5], concentrates on whole embryo culture system. Besides illustrating important methodological aspects and recent developments of the system, the authors summarize the growing literature supporting whole embryo culture as useful tool in assessing the embryotoxic potential of chemicals for regulatory purposes.…”
mentioning
confidence: 99%